Sea and Littoral Localities’ Economy: Exploring Potentialities for a Maritime Cluster - An Integrated Analysis of Huelva, Spain and Algarve, Portugal - Ortega, Cristina (2013)
As a littoral territory with more than 120 km of coast, Huelva (Andalusia, Spain) is a province that gives to marine and maritime activities a relevant role in its regional economy. The Algarve, the most southern region of mainland Portugal, bounded north and east by the regions of Alentejo and Huelva, also gives to the Sea importance in the main regional economic activities. In this article, we compare the emergence of policies for maritime clustering in both regions due to their geographical proximity that stimulate highly levels of cooperation. The relevance of the different type of policies being implemented in Huelva and the Algarve are analysed to a better comprehension of the similarities and the differences between these cases. The analysis of innovation actors, creating linkages between firms and scientific communities, focusing in marine sciences in scientific and technological networks, is crucial to understand the potential for the emergence of a dynamic trans-border cluster.